Analisa Potensi Energi Surya untuk Energi Listrik Banda Aceh dan Sekitarnya - Ahmad Syuhada; Zahrul Fuadi; Bayu Alif Satari (Jurnal Teknik Mesin Unsyiah, 2019)
Electrical energy crisis has become a common problem in Indonesia. Particularly Banda Aceh and surrounding areas, the impact of this phenomenon was a direct impact on the activities of the community. In general, Indonesia has a tropical climate that is potentially going to optimal utilization of solar energy. Particularly Banda Aceh and the surrounding in general have a geographical location in the coastal areas, which have the potential of solar energy potential. This study aims to analyze the potential value and also the effectiveness of solar energy, then analyze the electrical power generated by the solar cell in Banda Aceh and its surroundings. To determine the value of the potential of solar energy begins to measure and collect the value of the intensity of the sun. In case this is done by using the solar cell by measuring the intensity of the sun, current, voltage and temperature. This research was supported by the data collecting solar intensity value for 2 months at three different points, namely in Thermal Engineering Laboratory, BMKG Blang Bintang and SMK PPN Saree. This study degan manifold uses polycrystalline silicon solar cell with an area of 0.715 m2 solar intensity values obtained on October 27, 2016 amounted to 596 Watt / m2, and the output power of electricity by an average of 52.27 Watt. In  October 28, 2016 the average light intensity of 475 Watts / m2dan electric power output by an average of 31.37 Watt. In October 31, 2016 the average light intensity of 330 Watts / m2, and the output power of electricity by an average of 30.77 Watt. In 1 November 2016 the average light intensity of 686 Watts / m2, and the output power of electricity by an average of 50.93 Watt. In 2 November 2016 the average light intensity of 675 Watts / m2, and the output power of electricity by an average of 49.84 Watt.